Primary ependymoma of the retropubic space in a male patient. (20th November 2020) - Tasar Kapakli, Elif; Kosemehmetoglu, Kemal; Kaymaz, Figen; Akdogan, Bulent; Ozmen, Mustafa; Baydar, Dilek Ertoy
ABSTRACT: We report a case of primary intraabdominal ependymoma arising in the retropubic space of a male patient. An incidental intraabdominal mass was discovered in a 51-year-old man. Radiological studies revealed a 10 cm, solid and cystic tumor located in the Retzius fossa. Microscopically, the lesion was characterized by multiple cellular nodules composed of bland small cells forming true and pseudorosettes. No nuclear atypia, necrosis or increased mitotic activity was present. Neoplastic cells positive for AE1/3 and Cam5.2, and expressed patchy GFAP, and paranuclear dot-like to microvesicular EMA and D2-40, while S100, synaptophysin, PAX8, TLE1, WT1, inhibin, calretinin, Melan-A, and HMB45 were negative. Electron microscopy findings supported the diagnosis: 1) Frequent intracytoplasmic vacuoles with short and redundant microvilli and few cilia 2) lung intercellular junctions. The patient is alive with no evidence of disease for 4 years. Pathologists should be aware that rare extraneural ependymomas may occur in the Retzius space, even in a male patient. This entity should be kept in mind especially when the differential diagnosis is metastatic carcinoma with an unusual morphology and immune profile.